Intracranial Hemorrhage and Autoimmune Thrombocytopenia in a Neonate: A Rare "Unpredictable" Event. (5th April 2018) - Becocci, Andrea; Felice-Civitillo, Cristina; Laurent, Méryle; Boehlen, Françoise; De Luca, Roberta; Fluss, Joel
Neonatal thrombocytopenia is a rare complication of maternal autoimmune thrombocytopenia, and no maternal predictors of its gravity and potential complications have been identified. Neonatal cerebral hemorrhage, a feared event in the setting of autoimmune thrombocytopenia, is fortunately uncommon, but it can occur in utero or in the perinatal period, with potentially serious consequences. The authors report the case of a boy born to a mother affected by autoimmune thrombocytopenia, who presented with severe thrombocytopenia at birth and developed intracranial hemorrhage despite mild maternal thrombocytopenia at delivery and a prompt preventive treatment of the newborn. Platelet count should be tested at birth in all babies born from mothers with autoimmune thrombocytopenia, irrespective of maternal platelets counts during pregnancy or at delivery, and should be closely monitored during the first days of life. Systematic early and serial cranial ultrasound might be advocated in the setting of neonatal thrombocytopenia.